Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 58

Answer

$\dfrac{6^{-5}x^{-1}y^{2}}{6^{-2}x^{-4}y^{4}}=\dfrac{x^{3}}{216y^{2}}$

Work Step by Step

$\dfrac{6^{-5}x^{-1}y^{2}}{6^{-2}x^{-4}y^{4}}$ Evaluate the division: $\dfrac{6^{-5}x^{-1}y^{2}}{6^{-2}x^{-4}y^{4}}=6^{-5-(-2)}x^{-1-(-4)}y^{2-4}=6^{-3}x^{3}y^{-2}=...$ Simplify: $...=\dfrac{x^{3}}{6^{3}y^{2}}=\dfrac{x^{3}}{216y^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.